Studying changes in value relevance of accounting information Over Time (A Survey study on companies and banks listed on the Damascus Securities Exchange) - حموي, آيا; حيدر حيدر; همسه حمدان (Latakia University Journal - Economic and Legal Sciences Series, 2022)
This research provides empirical evidence from companies and banks listed in the Damascus Securities Exchange on the value relevance of accounting information represented by earning per share, book value and net cash flows, by measuring their ability to clarify changes in prices and thus predict those changes during the time period 2008-2020. The study methodology is to measure the value relevance by estimating a cross-sectional model of the variables in each of the study years and extracting the coefficient that expresses the suitability and then measuring the trend of development of this value during the studied period using a set of trend curves. The results of the cross-sectional regression showed that the best fit was achieved in 2019 with a rate of 92.3%, and the lowest was in 2009 with a rate of 1.23%. And by estimating a set of equations, it was concluded that the cubic equation represents the evolution of the adequacy of variables with time. Where the equation shows that the fit development goes through a positive development phase of 32.248 degrees, followed by a long-term decline of 6.143 degrees, followed by a positive development of 0.333 degrees. It is possible that the model reached in the research has an application benefit for investors by knowing when to rely on accounting variables in predicting price changes